Who expert committee on specifications for pharmaceutical preparations : forty-fifth report (WHO Technical Report Series, 2011)
General policy.--Join session with the expert Committee on Biological Standardization.--Quality control-specifications and test.--Quality control-international reference materials.--Quality control-national laboratories.--Quality assurance-good manufacturing practices.--Quality assurance-new approaches.--Quality assureance-distribution and trade of pharmaceuticals.--Prequalification of priority essential medicines.--Prequalification of quality control laboratories.--Prequalification of active pharmaceutical ingredient.--Regulatory guidance.--Numenclature, terminology and databases.--Summary and recomendations.